PHYSIOLOGICAL AND IMMUNOLOGICAL RESPONSES OF JAPANESE QUAILS TO OLEOBIOTIC - S.M. Beski, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was conducted to investigate the effect of the administration of oleobiotic to the drinking water of Japanese quails. Three different concentrations ofoleobiotic (0, 30 or 50 ml/1000L) were administrated in the drinking water and provided to the birds for 5 weeks. Throughout the five weeks experimental period, there was no significant effect of oelobiotic on the performance parameters including (feed intake, body weight, weight gain and FCR) of Japanese quail. The liver was heavier and there was a tendency of spleen to be heavier by rising levels of oleobiotic. Among the measured biochemical parameters of serum, the concentration of albumin increased in the birds that received the medium level of oleobiotic. The concentration of thyroid stimulating hormone in the serum decreased by rising level of oleobiotic in the drinking water of Japanese quails. Furthermore, the concentration of amylase in the serum decreased at the highest administration level of oleobiotic to the drinking water. As an essential oil, offering of oleobioticwas not promising regarding to the performance and physiology of Japanese quails when birds were raised in a relatively hygienic environment.Further researches are required to examine the efficacy of oleobiotic for poultry. Oleobiotic may expresses its beneficial effects during the bird exposure to highly pathogenic conditions.